2006
DOI: 10.1161/circulationaha.105.000695
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of the Symmetry Vein Graft Anastomosis Device

Abstract: Background— The Symmetry Bypass Connector (St. Jude Medical) was developed to rapidly anastomose saphenous vein grafts to the aorta during coronary bypass surgery (CABG) without cross-clamping. Previous uncontrolled studies of this device observed vein graft closures at six months, possibly attributable to neointimal hyperplasia. Methods and Results— To assess the long-term clinical outcomes of the Symmetry devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For nearly a century, suture-based vascular anastomoses have remained the gold standard despite their well-documented limitations. Numerous attempts have been made to develop alternatives to sutured vascular anastomosis because of the limitations of suture techniques when dealing with diseased or small vessels [11][12][13][14]33,34 . Here we demonstrate a new, nonmechanical and completely sutureless anastomosis technique capitalizing on the phase-transition properties of FDA-approved poloxamers and clinically used adhesives that is superior to the goldstandard hand-sewn anastomoses with respect to speed, patency in small vessels and long-term inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…For nearly a century, suture-based vascular anastomoses have remained the gold standard despite their well-documented limitations. Numerous attempts have been made to develop alternatives to sutured vascular anastomosis because of the limitations of suture techniques when dealing with diseased or small vessels [11][12][13][14]33,34 . Here we demonstrate a new, nonmechanical and completely sutureless anastomosis technique capitalizing on the phase-transition properties of FDA-approved poloxamers and clinically used adhesives that is superior to the goldstandard hand-sewn anastomoses with respect to speed, patency in small vessels and long-term inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Kachy et al reported clinical outcomes of the Symmetry vein graft anastomosis device in a matched case-control study. 16 Their analyses showed a trend toward an increased risk for major adverse events at 1 year (p ¼ 0.053) and the authors suggested that this could be attributed to early graft closure. The present study demonstrates that this potential negative effect of the Symmetry device did not prove to be the case during a longer period of follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…One such device allowed rapid vein graft anastomosis with the aorta without the need for cross-clamping. However, the higher risk of adverse outcome, including early graft closure precluded its wide spread adoption (10) .…”
Section: Operative Datamentioning
confidence: 99%